Динаміка ландшафтних насаджень балки “Боговщина” та узбережжя лебединого ставу дендропарку “Тростянець” - Ilyenko, A.A.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The results of studying of landscape compositions, dynamics of number, specific structure and spatial structure of wood plantings of the ravine Bogovshchina and coasts of Lebediny pond of arboretum Trostyanets 1957–2007 years are presented.